Balancing Tradition and Science: Acupuncture in Pain Control - Alicja Grzelak (Journal of Education, Health and Sport)
Introduction: Pain management is a critical component of healthcare, addressing acute and chronic conditions that significantly impact quality of life. Traditional pharmacological approaches, while effective, often present side effects and dependency risks. Acupuncture, rooted in traditional Chinese medicine, has emerged as a complementary and alternative therapy, leveraging the body’s natural mechanisms to alleviate pain through the strategic insertion of fine needles at acupoints.